Some balancing considerations about Slavic and Baltic - Eckert, Rainer (Baltistica, 2023)
The article describes some characteristic features of my teaching and research on the ancient terminology of beekeeping in Slavic and Baltic languages. Some recent materials and corrections of earlier works are cited.